A state‐price volatility index for the U.S. government bond market. (24th April 2017) - Pan, Zheyao
Abstract: Using the Arrow–Debreu state‐contingent pricing methodology, this paper derives a U.S. government bond market volatility index (GBVX ) . I show that GBVX is an unbiased predictor for the next 30 day realised volatility of the Treasury note futures return. GBVX also subsumes the information of GARCH, EWMA and historical volatility measures. Furthermore, GBVX serves as an effective predictor for the future realised volatilities of a wide class of fixed income portfolios. The results suggest GBVX as a powerful instrument for volatility forecasting in the fixed income markets.